Solving a continuous multifacility location problem by DC algorithms. (2nd January 2022) - Bajaj, Anuj; Mordukhovich, Boris S.; Nam, Nguyen Mau; Tran, Tuyen
ABSTRACT: The paper presents a new approach to solve multifacility location problems, which is based on mixed integer programming and algorithms for minimizing differences of convex (DC) functions. The main challenges for solving the multifacility location problems under consideration come from their intrinsic discrete, nonconvex, and nondifferentiable nature. We provide a reformulation of these problems as those of continuous optimization and then develop a new DC type algorithm for their solutions involving Nesterov's smoothing. The proposed algorithm is computationally implemented via MATLAB numerical tests on both artificial and real data sets.